Intrusive luxation in primary teeth - Review of literature and report of a case - Megha Gupta (Elsevier, 2011)
Luxation injuries such as intrusion are commonly seen in the primary dentition. Intrusion drives the tooth deeper into the alveolar socket, which results in damage to the pulp and peridontium. Difficulty in gaining compliance from a very young child and the risk of damaging the permanent tooth germ makes the management of these injuries challenging. Careful clinical and radiographic examination along with regular follow-up is essential. A case of intrusive luxation to the maxillary central incisor in a 3-year-old patient is reported. Spontaneous reeruption was noted 4 months after injury, but the tooth had developed an abscess and external root resorption. Hence, extraction of the tooth was done and an anterior esthetic fixed space maintainer was placed. Traumatic injuries to the primary dentition should not be ignored by the parents or by the dentist. The paper also includes a literature review of intrusive luxation in the primary dentition. Keywords: Intrusive luxation, Dental trauma, Primary dentition, Re-eruption, Tooth intrusion, Anterior esthetic fixed space maintainer